On the Fictitious Grease Lubrication Performance in a Four-Ball Tester - Sravan K. Joysula; Anshuman Dube; Debdutt Patro; Deepak Halenahally Veeregowda (Lubricants, 2021)
The extreme pressure (EP) behavior of grease is related to its additives that can prevent seizure. However, in this study following ASTM D2596 four-ball test method, the EP behavior of greases was modified without any changes to its additive package. A four-ball tester with position encoders and variable frequency drive system was used to control the speed ramp up time or delay in motor speed to demonstrate higher grease weld load and lower grease friction that were fictitious. A tenth of a second delay in speed ramp up time had showed an increase in the weld load from 7848 N to 9810 N for grease X and 6082 N to 9810 N for grease Y. Further increase in the speed ramp up time to 0.95 s showed that the greases passed the maximum load of 9810 N that was possible in the four-ball tester without seizure. The mechanism can be related to the delay in rise of local temperature to reach the melting point of steel required for full seizure or welding, that was theoretically attributed to an increase in heat loss as the speed ramp-up time was increased. Furthermore, the speed ramp up time increased the corrected load for grease X and Y. This resulted in lower friction for grease X and Y. This fictitious low friction can be attributed to decrease in surface roughness at higher extreme pressure or higher corrected load. This study suggests that speed ramp up time is a critical factor that should be further investigated by ASTM and grease manufacturers, to prevent the use of grease with fictitious EP behavior.